BIOTECHNOLOGY IN SUSTAINABLE AGRICULTURE: GENETIC MODIFICATIONS AND THEIR IMPLICATIONS FOR ECO-FRIENDLY FARMING SOLUTIONS - Muhammad Hazmi; Natasha Harris; Michael Jordan (Yayasan Adra Karima Hubbi, 2026)
Biotechnology has emerged as a critical response to the growing challenges of sustainable agriculture, particularly in addressing food security, environmental degradation, and resource inefficiency. Increasing demand for agricultural productivity has intensified pressure on ecosystems, necessitating innovative solutions that balance yield improvement with ecological preservation. This study aims to examine the role of genetic modifications in advancing eco-friendly farming solutions, focusing on their contributions to productivity, resource efficiency, and environmental sustainability. A mixed-methods research design was employed, integrating quantitative analysis of agronomic and environmental indicators with qualitative insights from farmers and stakeholders across diverse agroecological regions. Data were collected from 120 farming units and analyzed using descriptive, inferential, and thematic techniques to ensure comprehensive interpretation. Results indicate that genetically modified crops significantly enhance yield stability, reduce pesticide usage, and improve water-use efficiency, while also contributing to better soil quality and biodiversity outcomes when integrated with sustainable practices. Findings further reveal that adoption is influenced by knowledge, regulatory clarity, and contextual compatibility. This study concludes that genetic modifications can function as a complementary component within sustainable agriculture, provided they are implemented within an ecologically informed framework. Evidence underscores the importance of integrative approaches that align technological innovation with environmental and social considerations.